Nonlinear Structural Behavior of RC Frames Integrated to Inner Steel Frame by Shear Connectors - NADİLOUEİ, MİR HADİ RASOULİ (İstanbul Kültür Üniversitesi, 2022)
Reinforced concrete frames can be upgraded using steel inner frames connected by different types of shear connectors such as studs, bolts, angles U shape profiles, or steel cushions which are recently appeared in the literature. That is not only important to achieve higher earthquake resisting capacities but also important to retrofit the poorly designed and constructed reinforced concrete structures in earthquake-prone areas. The response of a reinforced concrete structure to an earthquake excitation will be altered by the inner steel frame depending on its lateral rigidity and strength in addition to the type, the rigidity, the strength, energy-absorbing capability, the orientation with respect to peripheral elements, etc. of shear connectors. The effects of all these parameters on the overall behavior of the combined structure consisting of the reinforced concrete frame and steel frame and shear connectors are investigated in this study to better understand the complete redesign process. The nonlinear behavior of each element is inevitably taken into consideration in this study to see whether it would be possible to reach the limit loads without having had an early failure such as exceeding the local ductility and buckling of steel diagonals which are important to reaching cost-effective retrofitting. A couple of different structural models are defined to observe the possible structural behaviors of combined frames for that purpose and the very well-known computer program SAP2000 was employed for parametrical works. Special attention has been exercised on the shear connectors in this work. And not only push-over analysis but also step-by-step integration are carried out by choosing several reel earthquakes which are scaled so that code compatible they became. It can be concluded that the earthquake resistance of an existing structure can be reliably upgraded by steel inner frames in a cost-effective manner and the energyabsorbing capacities are increased by properly used shear connectors.
▪ Yüksek lisans tezi.